Giving Grants from Parents to Their Children According to the Compilation of Islamic Law and the Civil Code - Borkat Halomoan Siregar; Ahmad Rezy Meidina (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This article examines the gifts that parents give to their children. Grants in the perspective of classical fiqh are giving an object voluntarily and without reward from someone to another who is still alive to own it. The concept of grants is currently changing, in practice, many grants that are given are then canceled by the grantor for various reasons, for example, the recipient of the grant has bad behavior or has a spendthrift spirit. This was known after the grant was given. Even though the person previously displayed good behavior but then changed with the changing times. Fundamentally, the author is interested in this research, using a statute approach by examining the Civil Code and the Compilation of Islamic Law as well as Government Regulation Number 37 of 1998 concerning regulations for the position of Land Deed Making Officer. The research method used is Normative juridical with the aim that writers and readers can find out about the arrangements for granting and the legal consequences of canceling a grant according to the Compilation of Islamic Law and the Civil Code and provide several benefits, namely for scientific development in the field of law in general, as well as contributing thoughts and understanding of grantmaking.